Answer:
Simplifying
-8p2 + -4p = -4
Reorder the terms:
-4p + -8p2 = -4
Solving
-4p + -8p2 = -4
Solving for variable 'p'.
Reorder the terms:
4 + -4p + -8p2 = -4 + 4
Combine like terms: -4 + 4 = 0
4 + -4p + -8p2 = 0
Factor out the Greatest Common Factor (GCF), '4'.
4(1 + -1p + -2p2) = 0
Factor a trinomial.
4((1 + -2p)(1 + p)) = 0
Ignore the factor 4.
Subproblem 1
Set the factor '(1 + -2p)' equal to zero and attempt to solve:
Simplifying
1 + -2p = 0
Solving
1 + -2p = 0
Move all terms containing p to the left, all other terms to the right.
Add '-1' to each side of the equation.
1 + -1 + -2p = 0 + -1
Combine like terms: 1 + -1 = 0
0 + -2p = 0 + -1
-2p = 0 + -1
Combine like terms: 0 + -1 = -1
-2p = -1
Divide each side by '-2'.
p = 0.5
Simplifying
p = 0.5
Subproblem 2
Set the factor '(1 + p)' equal to zero and attempt to solve:
Simplifying
1 + p = 0
Solving
1 + p = 0
Move all terms containing p to the left, all other terms to the right.
Add '-1' to each side of the equation.
1 + -1 + p = 0 + -1
Combine like terms: 1 + -1 = 0
0 + p = 0 + -1
p = 0 + -1
Combine like terms: 0 + -1 = -1
p = -1
Simplifying
p = -1
Solution
p = {0.5, -1}
Simplifying
-8p2 + -4p = -4
Reorder the terms:
-4p + -8p2 = -4
Solving
-4p + -8p2 = -4
Solving for variable 'p'.
Reorder the terms:
4 + -4p + -8p2 = -4 + 4
Combine like terms: -4 + 4 = 0
4 + -4p + -8p2 = 0
Factor out the Greatest Common Factor (GCF), '4'.
4(1 + -1p + -2p2) = 0
Factor a trinomial.
4((1 + -2p)(1 + p)) = 0
Ignore the factor 4.
Subproblem 1
Set the factor '(1 + -2p)' equal to zero and attempt to solve:
Simplifying
1 + -2p = 0
Solving
1 + -2p = 0
Move all terms containing p to the left, all other terms to the right.
Add '-1' to each side of the equation.
1 + -1 + -2p = 0 + -1
Combine like terms: 1 + -1 = 0
0 + -2p = 0 + -1
-2p = 0 + -1
Combine like terms: 0 + -1 = -1
-2p = -1
Divide each side by '-2'.
p = 0.5
Simplifying
p = 0.5
Subproblem 2
Set the factor '(1 + p)' equal to zero and attempt to solve:
Simplifying
1 + p = 0
Solving
1 + p = 0
Move all terms containing p to the left, all other terms to the right.
Add '-1' to each side of the equation.
1 + -1 + p = 0 + -1
Combine like terms: 1 + -1 = 0
0 + p = 0 + -1
p = 0 + -1
Combine like terms: 0 + -1 = -1
p = -1
Simplifying
p = -1
Solution
p = {0.5, -1}
Explanation: